Pengaruh Agresivitas Pajak Pada Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Pemoderasi - Devi, Putu Nirmala Chandra; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 22 No 3 (2018), 2018)
Getting maximum firm value, can be achieved by tax aggressiveness. However, this tax aggressiveness is could lead to agency conflicts between the manager and shareholders. Firm size is expected to minimize agency conflicts that occur and can increase the value of the firm . This study aims to obtain empirical evidence about the influence of tax aggressiveness on firm value and the role of firm size in moderating the influence of tax aggressiveness on firm value. This research was conducted at property and real estate company which listed in Indonesian Stock Exchange in 2012-2016 using non probability sampling method with purposive sampling as sample selection method. The number of samples is 65 samples. Data analysis technique used is Moderated Regression Analysis (MRA). The result of this analysis is tax aggressiveness negatively affect of the firm value and the firm size weakens the influence of tax aggressiveness on the firm value . Keywords:  firm value, tax aggressiveness, firm size